2023 All-Russian screening for hypertension: results - O. P. Rotar; I. N. Ilyanova; M. A. Boyarinova; E. V. Moguchaya; K. M. Tolkunova; V. A. Dyachkov; O. A. Rubanenko; A. O. Rubanenko; O. E. Gaberman; E. Yu. Gubareva; B. V. Pomogaibo; E. M. Dolya; et al. (Российский кардиологический журнал, 2024)
Aim. To assess awareness of blood pressure (BP) level, adherence to therapy and achievement of target BP in residents of Russian regions as part of the 2023 hypertension (HTN) screening campaign.Material and methods. During May 2023, 4613 participants from 23 cities of Russia took part in the screening. Participation was voluntary without restrictions on sex. All patients aged over 18 years. During screening, BP and pulse were measured three times using automatic or mechanical BP monitors, and a questionnaire about behavioral risk factors, concomitant diseases and therapy was filled out. HTN was diagnosed with systolic BP ≥140 mm Hg and/or diastolic BP ≥90 mm Hg and/or taking antihypertensive therapy (AHT).Results. The analysis included data from 4585 respondents aged 18 to 95 years with an average age of 45 [28;59] years, of which 1729 were men (37,7%). The proportion of hypertensive patients was 49,6%. Among them, 62,8% took AHT and achieved target BP in 76,6% and 45,7% with the target BP criterion <140/90 mm Hg and <130/80 mm Hg, respectively. Most patients took dual AHT (37,4%), while monotherapy and triple therapy was registered in 27,5% and 23,4%, respectively. Initiation of therapy was performed with combination AHT in 43,7% of patients with HTN and 41,4% are currently using fixed-dose combination therapy. On-demand therapy was the most common reason for skipping medications and was more common in women, while men more often cited the high drug cost and a history of adverse reactions. Among patients with HTN, home BP measurement was associated with a higher prevalence of achieving target BP as follows: 1000 (60%) vs 100 (17%), p<0,001.Conclusion. The data obtained indicate, on the one hand, a continuing insufficient level of awareness about high BP and the use of antihypertensive drugs among the population, but there is a tendency to improve the effectiveness of the treatment of hypertension, including the use of fixed-dose combinations of antihypertensive drugs.